High incidence of skewed X chromosome inactivation in young patients with familial non-BRCA1/BRCA2 breast cancer. Issue 11 (6th May 2005) - Kristiansen, M; Knudsen, G P S; Maguire, P; Margolin, S; Pedersen, J; Lindblom, A; Ørstavik, K H
Abstract : Background: A higher frequency of skewed X chromosome inactivation has been reported in a consecutive series of young patients with breast cancer compared with controls of a similar age. Objective: To investigate the X inactivation pattern in patients with familial non- BRCA1 / BRCA2 breast cancer (n = 272), BRCA1 / BRCA2 germline mutations (n = 35), and sporadic breast cancer (n = 292). Methods: X inactivation pattern was determined by polymerase chain reaction analysis of the highly polymorphic CAG repeat in the androgen receptor ( AR ) gene. The X inactivation pattern was classified as skewed when 90% or more of the cells preferentially expressed one X chromosome. Results: Young patients with familial breast cancer had a significantly higher frequency of skewed X inactivation (11.2%) than young controls (2.7%) (p = 0.001). There was also a strong tendency for middle aged patients with sporadic breast cancer to be more skewed than middle aged controls (13.6% v 4.4%) (p = 0.02). No association between skewed X inactivation and breast cancer was found for the BRCA1 / BRCA2 patients . Conclusions: Skewed X inactivation may be a risk factor for the development of breast cancer in both sporadic and familial breast cancer and may indicate an effect of X linked genes.